Factors triggering the oral mucosal lesions by complete dentures - TÜRKER, ŞEBNEM BEGÜM; ÖZKAN, YASEMİN (ELSEVIER IRELAND LTD, 2010)
Oral mucosal lesions may represent acute or chronic reactions to factors related with dentures. The aim of this study was to determine the frequency of the oral lesions related to gender, age, the length of time of denture usage, the balance of denture and cleaning methods and frequency. The 106 patients who have old complete dentures came to the Dental Faculty of Marmara University, Istanbul (Turkey) to have new complete dentures were asked to participate in the investigation. The subjects (51 men and 55 women) were 37-80 years of age with a mean age of 60.28 +/- 10.52 years. All main factors were estimated in subgroups: cleaning methods and frequency were divided into 3 subgroups respectively as toothbrush and toothpaste/soap, denture cleansing tablets and sodium carbonate, and 3 times a day, everyday, every 3 day and once a week. The data obtained was evaluated by One-way ANOVA, Mann-Whitney U-test, Kruskal-Wallis-test, Student t-test and chi(2)-test. The level of statistical significance was set at p < 0.05. The patients displayed statistically significant differences in the topics of the length of time of denture usage and the balance of denture in terms of retention. The complete denture wearers should be educated in the importance of periodic examination due to the changing of supporting tissues for detection early mucosal lesions to maintain their oral and dentures hygiene in optimum level. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: Complete denture; Oral mucosal lesions; Oral and dentures hygiene; FIBROUS INFLAMMATORY HYPERPLASIA; HEALTH; SATISFACTION; PREVALENCE; MANAGEMENT; WEARERS; POPULATION; STOMATITIS; DENTISTRY; ETIOLOGY